2004
DOI: 10.1055/s-2004-825728
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-stimulating Factor Synergistically Augments 1,25-Dihydroxyvitamin D3-Induced Monocytic Differentiation in Murine Bone Marrow Cell Cultures

Abstract: In a series of studies, we have reported that 1,25-dihydroxyvitamin D (3), a known stimulator of monocytic differentiation, primes bone marrow progenitor cells or promyelocytic HL-60 cells to the actions of several factors involved in both monocytic and granulocytic differentiation. In the present study, we have further examined the combinational effects of 1,25-dihydroxyvitamin D (3) and the other inducer of granulopoiesis, granulocyte colony-stimulating factor, on non-fractionated native murine bone-marrow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The differentiation of monocytes to macrophages and their fusion to form giant cells, induced by the 1,25(OH) 2 D 3 , has been well documented experimentally. 1, 14, 15, 20, 21 The proliferation of macrophages and multinucleated giant cells in the present study could be the response of these cells to the action of the 1,25(OH) 2 D 3 present in S. glaucophyllum . Such action has been suggested in similar infiltrates in the muscle layer of the stomach of rabbits experimentally poisoned with the same plant 18 and in arteries and lungs of sheep with enzootic calcinosis induced by the calcinogenic plant Nierembergia veitchii .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The differentiation of monocytes to macrophages and their fusion to form giant cells, induced by the 1,25(OH) 2 D 3 , has been well documented experimentally. 1, 14, 15, 20, 21 The proliferation of macrophages and multinucleated giant cells in the present study could be the response of these cells to the action of the 1,25(OH) 2 D 3 present in S. glaucophyllum . Such action has been suggested in similar infiltrates in the muscle layer of the stomach of rabbits experimentally poisoned with the same plant 18 and in arteries and lungs of sheep with enzootic calcinosis induced by the calcinogenic plant Nierembergia veitchii .…”
Section: Discussionmentioning
confidence: 52%
“…The participation of 1,25(OH) 2 D 3 in the differentiation of monocytes to macrophages and fusion to form multinucleated giant cells has been extensively studied. 1, 11, 14, 15, 21 Infiltration of macrophages and multinucleated giant cells in lung, arteries, stomach, and heart were described in natural and experimental calcinosis induced by calcinogenic plants 24, 18, 28, 37, 41 that contain high levels of 1,25(OH) 2 D 3 as a glycoside derivative. 40…”
mentioning
confidence: 99%
“…Vitamin D3 has a range of physiological functions in the body, the most important being the maintenance of the calcium and phosphorus balance [14] in osteoblasts, where it usually inhibits cellular proliferation and induces differentiation [15]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to its hormonal action on calcium metabolism, 1, 25(OH) 2 D3 has been known as an inducer of leukocyte differentiation, stimulating the differentiation of bone marrow progenitor cells or HL60 cells toward monocyte/macrophage lineage [20,21]. It was reported that 1,25(OH) 2 D3 also participated in the growth arrest, apoptosis or differentiation of other cancer cells, such as prostate and thyroid cancers [22,23].…”
Section: Introductionmentioning
confidence: 97%